2020
DOI: 10.1177/1120672120949101
|View full text |Cite
|
Sign up to set email alerts
|

Duration of contact lens removal before myopic refractive surgery

Abstract: Purpose: To compare refractive surgery outcomes in patients with different periods without contact lenses prior laser surgery. Materials and methods: Patients included in this study underwent myopic keratorefractive laser surgery between January 2005 and December 2014. Patients were divided into three groups based on the duration of time passed free of soft contact lens wearing prior to final preoperative evaluation and surgery (<24 h, 1–3 days or >3 days). Spectacle wearers served as a control group. Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…The main focus of this study was to compare the outcomes of a speci c refractive surgical modality, LASIK, after discontinuation of SCL in a large sample of patients. However, only two other studies have focused on SCL removal and refractive surgery in general [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main focus of this study was to compare the outcomes of a speci c refractive surgical modality, LASIK, after discontinuation of SCL in a large sample of patients. However, only two other studies have focused on SCL removal and refractive surgery in general [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many recommendations and guidelines have proposed the removal of SCL at least 3 to 14 days before LASIK, but still, there are no consensus [16,17]. Shehadeh-Mashor et al [14], in their casecontrol study concerning the duration of SCL removal before myopic refractive surgery, have found a signi cant difference between the patients who removed their SCL in less than 1 day and those who removed them in more than 1 day before the PRK procedure. However, they found no signi cant difference between those who discontinued the SCL between 1 to 3 days and those who discontinued them for more than 3 days before PRK.…”
Section: Discussionmentioning
confidence: 99%
“…Cases with mesopic pupil diameter > 6 mm or patients whose eyes could not belong to the same treatment group because of differing ablation depths were also excluded. Patients using contact lenses were asked to stop wearing their lenses for 1–2 and 3–4 weeks preoperatively for soft and hard lenses, respectively [ 14 ]. Masking was followed appropriately; the surgeon, person performing specular microscopy, and the person who read and interpreted the printout reports of specular microscopy were masked.…”
Section: Methodsmentioning
confidence: 99%
“…The corneal epithelial thickness can increase following discontinuation of SCL wear; however, the corneal epithelial thickness is unable to reach the normal range exhibited by people without SCL wear ( 11 ). A previous study ( 12 ) demonstrated that the corneal epithelial thickness reached stability following discontinued wear of SCLs within 2 weeks; nevertheless, individual variation should not be discounted.…”
Section: Introductionmentioning
confidence: 95%